ANALISIS PENERAPAN AKUTANSI AKRESI PADA USAHA BUDIDAYA IKAN LELE DENGAN PERSYARATAN STANDAR AKUTANSI (PSAK) 241 DI KABUPATEN MOJOKERTO - Irza Fajrul Falah (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this research is to analyze the application of accrual accounting in tilapia farming businesses in Mojokerto Regency and its alignment with the applicable Financial Accounting Standards (FAS), particularly FAS 241. Tilapia farming is one of the rapidly growing economic sectors in the region, but it has not fully adopted formal accounting principles, including accrual accounting related to the changes in biological asset values. The research used a qualitative approach with a case study method, focusing on 9 tilapia farming businesses in Mojokerto Regency, specifically in Mojoanyar and Puri districts. Data was collected through interviews, questionnaires, and document analysis. The findings show that most of the business operators have not systematically applied accrual accounting in their financial records. This is due to a lack of understanding of accounting standards and the absence of support from relevant parties. The research recommends the need for awareness campaigns and training on accrual accounting and the comprehensive implementation of FAS 241 to improve the transparency and accountability of financial reports. As a result, tilapia farming businesses can be better prepared to face market challenges and obtain better access to financing.